Low Birth Weight and Prematurity Are Associated with Hypertensive Disorder of Pregnancy in Later Life: A Cross-Sectional Study in Japan - Kurabayashi, Takumi; Mizunuma, Hideki; Kubota, Toshiro; Nagai, Kazue; Hayashi, Kunihiko (American Journal of Perinatology, 2020)
Objective We previously reported that hypertensive disorder of pregnancy (HDP) was a risk factor for hypertension and hypercholesterolemia in later life. Additionally, the age-adjusted odds ratio (OR) of HDP was 2.72 for Japanese women whose mothers had a history of HDP versus those whose mothers did not. This study aimed to clarify the association of HDP with birth weight and gestational age.Study Design A self-administered baseline survey of the Japanese Nurses' Health Study (JNHS) cohort was conducted from 2001 to 2007. Data on 17,278 parous female nurses who knew their own birth weights were extracted from the JNHS baseline survey (n = 49,927) and subjected to cross-sectional, retrospective analysis. Data on weeks of gestation, birth weight, and history of HDP were collected.Results The age-adjusted ORs for HDP were 1.62 (95% confidence interval [CI]: 1.20–2.19) for birth weight <2,000 g, 1.24 (CI: 1.04–1.48) for 2,000 to 2,499 g, 1.11 (CI: 1.00–1.23) for 2,500 to 2,999 g, and 1.08 (CI: 0.94–1.24) for ≥3,500 g compared with 3,000 to 3,499 g. The age-adjusted ORs for HDP were 1.27 (95% CI: 1.04–1.54) for a gestational age < 37 weeks and 0.93 (0.70–1.23) for ≥42 weeks compared with 37–41 weeks. The age-adjusted OR of the birth weight score for HDP in later life was 0.98 (CI: 0.94–1.03; Cochran–Armitage trend test: z = 0.401, p = 0.688).Conclusion Among women in Japan, a history of low birth weight and prematurity are risk factors for HDP in later life. The risk of HDP among women born with low birth weight and/or premature deserves attention.
Keywords: low birth weight; prematurity; hypertensive disorder of pregnancy; Japanese Nurses' Health Study